Niektóre praktyczne wyzwania w modelowaniu wielowymiarowych procesów GARCH - Piontek, Krzysztof (Some practical challenges in multivariate GARCH modelling, 2006)
The article presents some information about selected Multivariate GARCH Models and challenges in practical application of those models. Main attention is paid here to the following problems: number of parameters to estimate, positivedefiniteness and stationarity condition for covariance matrix. Full and diagonal VECH models, as well as full, diagonal and scalar BEKK models, are considered. The results obtained from the empirical research indicate that the 2- dimensional diagonal VECH model is optimal for the most data- sets. The results can be applied to time-varying hedge ratio estimate.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 194-205